Kajian Tentang Nyamuk Aedes aegypti di Daerah Dataran Rendah dan Dataran Tinggi di Kabupaten Karanganyar Tahun 2003 - Wahyuningsih, Sri; Nurjazuli, Nurjazuli; Suhartono, Suhartono (Jurnal Kesehatan Lingkungan Indonesia, 2004)
ABSTRACT Background : The Aedes aegypti mosquito is  a vector of DHF that influenced by temperature and humidity, because the lower and the higher make them can not survive. The degree of different location will result the different temperature and humidity. The Ngringo village of Jaten sub districtis is located at 98 meters over surface sea level and Karanganyar village of Karanganyar sub district is 480 meters over surface sea leve, they are the endemic village of DHF. In 2003, the Ngringo village had IR = 0,75 per 10,000 population and  Karanganyar village was not found DHF cases. The objective of this research is to analyze characteristic difference of areas any at both high and low landscape. Methods : This is an observational research using cross sectional design. The sample is 30 houses on Ngringo village and 30 houses on Karanganyar village, by apllied ovitrap, larvae survey and capturing of Aedes Aegypti mosquitoes at the resting places surround the houses. Then, surgering was done to know parousity and dilatation. Data would be analyzed using chi square test at a = 0,05. Results : The research found that the proportion of  indoor and  outdoor, the mosquito mosquito eggs , larvae, mosquitoes adult, parous mosquitoes and dilatation mosquitoes are more found at the low landscape than the high one. There is a difference of proportion of egg finding indoor (p = 0,001) between  in the low landscape and the high one. There is no difference of proportion of egg finding outdoor (p = 0,09) between in the low landscape and the high one. There is a difference of proportion of larvae finding (p = 0,001) between  in the low landscape and the high one. There is a difference of proportion adult mosquitoes finding (P= 0,001) between in the low landscape and the high one. There is a difference of proportion of parous mosquitoes finding (p = 0,001) between in the low landscape and the high one and there is no difference  of proportion of dilatation mosquitoes finding (p = 1,00) between in the low landscape and the high one. Conclusions : Same characteristics of mosquito are different between at the low and the high landscape.They are found higher at the low than the high landscape. Key word :  Aedes aegypti mosquitoes, low and high landscape, Karanganyar, 2003.